Stereotactic cavity irradiation or whole-brain radiotherapy following brain metastases resection: outcome, prognostic factors, and recurrence patterns - El-Shafie, Rami; Kronsteiner, Dorothea; Schmitt, Daniela; Uzun-Lang, Kristin; König, Laila; Höne, Simon; Forster, Tobias; Nettelbladt, Bastian von; Eichkorn, Tanja; Adeberg, Sebastian; Debus, Jürgen; Rieken, Stefan (Frontiers in oncology, 2020)
Introduction: Following the resection of brain metastases (BM), whole-brain radiotherapy (WBRT) is a long-established standard of care. Its position was recently challenged by the less toxic single-session radiosurgery (SRS) or fractionated stereotactic radiotherapy (FSRT) of the resection cavity, reducing dose exposure of the healthy brain. Patients and methods: We analyzed 101 patients treated with either SRS/FSRT (n=50) or WBRT (n=51) following BM resection over a 5-year period. Propensity score adjustment was done for age, total number of BM, timepoint of BM diagnosis, controlled primary and extracranial metastases. A Cox Proportional Hazards model with univariate and multivariate analysis was fitted for overall survival (OS), local control (LC) and distant brain control (DBC). Results: Median patient age was 61 (IQR: 56-67) years and the most common histology was non-small cell lung cancer, followed by breast cancer. 38% of the patients had additional unresected BM. 24 patients received SRS, 26 patients received FSRT and 51 patients received WBRT. Median OS in the SRS/FSRT subgroup was not reached (IQR NA-16.7 months) versus 12.6 months (IQR 21.3-4.4) in the WBRT subgroup (HR 3.3, 95%-CI:[1.5;7.2] p<0.002). 12-months LC-probability was 94.9% (95%-CI:[88.3;100.0]) in the SRS subgroup versus 81.7% (95%-CI:[66.6;100.0]) in the WBRT subgroup (HR 0.2, 95%-CI:[0.01;0.9] p=0.037). 12-months DBC-probabilities were 65.0% (95%-CI:[50.8;83.0]) and 58.8% (95%-CI:[42.9;80.7]), respectively (HR 1.4, 95%-CI:[0.7;2.7] p=0.401). In propensity score-adjusted multivariate analysis, incomplete resection negatively impacted OS (HR 3.9, 95%-CI:[2.0;7.4], p<0.001) and LC (HR 5.4, 95%-CI:[1.3;21.9], p=0.018). Excellent clinical performance (HR 0.4, 95%-CI:[0.2;0.9], p=0.030) and better graded prognostic assessment (GPA) score (HR 0.4, 95%-CI:[0.2;1.0], p=0.040) were prognostic of superior OS. A higher number of BM was associated with a greater risk of developing new distant BM (HR 5.6, 95%-CI:[1.0;30.4], p=0.048). In subgroup analysis, larger cavity volume (HR 1.1, 95%-CI:[1.0;1.3], p=0.033) and incomplete resection (HR 12.0, 95%-CI:[1.2;118.3], p=0.033) were associated with inferior LC following SRS/FSRT. Conclusion: This is the first propensity score-adjusted direct comparison of SRS/FSRT and WBRT following the resection of BM. Patients receiving SRS/FSRT showed longer OS and LC compared to WBRT. Future analyses will address the optimal choice of safety margin, dose and fractionation for postoperative stereotactic RT of the resection cavity.
Gesehen am 10.08.2020